Analysis Of Student Learning Independence In The Implementation Of UKBM (Independent Learning Activities Units) In Learning Chemistry Hydrocarbon Material - Hasibuan, Desy Rahmayanti (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Study This aim For know application of UKBM Chemistry and independence Study student in implementation of UKBM. Study This carried out at MAN 2 Padang Lawas. Study This is study qualitative with method approach quantitative . Subject in study This is class XI MIA 1, XI MIA 2 and XI MIA 3 where third class the in learning chemistry Already using UKBM Chemistry. Data collection techniques were carried out with interviews , observations , and questionnaires . Research result obtained : 1) Based on results interview with Vice Principal Curriculum and eyes lesson chemistry concluded implementation of UKBM Chemistry is underway with well and have been in accordance with instruction technical from government . The implementation of UKBM Chemistry is ongoing with Good seen from results observation by 70% and results evaluation checklist sheet by 85%. 2) Based on results interview with an eye teacher lesson chemistry , students can Study independent in accordance with UKBM flow that has been arranged . Based on the results of the questionnaire, the level of student learning independence in chemistry learning is in the good category at 78.66%. From this data it can be concluded that student learning independence in implementing UKBM in Chemistry Learning for class XI MIA MAN 2 Padang Lawas can be said to be good.